"Top hat" versus conventional loop electrosurgical excision procedure in women with a type 3 transformation zone - Chumnan Kietpeerakool (2018)
Objective: To compare the "top-hat" and conventional loop electrosurgical excision procedures (LEEP) performed in women with a type 3 transformation zone to assess the rate of endocervical margin involvement. Methods: Women with a type 3 transformation zone randomly allocated into the conventional (n = 94) and top-hat LEEP (n = 86) groups were analyzed. Results: The rate of endocervical margin involvement in the top-hat group was lower than that in the conventional group (32.6% vs 53.2%; RR 0.36; 95% CI, 0.19-0.68; P = 0.003). Among women with positive endocervical margins, women undergoing top-hat LEEP were less likely to have residual lesions compared with those in the conventional group (52.2% vs 84.1%, respectively, P = 0.04). There was no significant difference in the complication rate between the top-hat and conventional groups (7.0% vs 10.6%, respectively, P = 0.39). Conclusion: Top-hat LEEP performed in women with a type 3 transformation zone reduces the risks of endocervical margin involvement and residual diseases compared with conventional LEEP, with no significant difference in perioperative complications. © 2009 International Federation of Gynecology and Obstetrics.